Home-based cognitive training in pediatric patients with acquired brain injury: preliminary results on efficacy of a randomized clinical trial - Corti, Claudia (Sci Rep, 2020)
Cognitive rehabilitation may compensate for cognitive deficits of children with acquired brain injury (ABI), capitalizing on the use-dependent plasticity of a developing brain. Remote computerized cognitive training (CCT) may be delivered to patients in ecological settings, ensuring rehabilitation continuity. This work evaluated cognitive and psychological adjustment outcomes of an 8-week multi-domain, home-based CCT (Lumosity Cognitive Training) in a sample of patients with ABI aged 11–16 years. Two groups of patients were engaged in five CCT sessions per week for eight weeks (40 sessions). According to a stepped-wedge research design, one group (Training-first Group) started the CCT immediately, whereas the other group (Waiting-first Group) started the CCT after a comparable time of waiting list. Changes after the training and after the waiting period were compared in the two groups. Both groups improved in visual-spatial working memory more after the training than after the waiting-list period. The Training-first group improved also in arithmetic calculation speed. Findings indicate that a multi-domain CCT can produce benefits in visual-spatial working memory, probably because, in accordance with previous research, computer games heavily tax visuo-spatial abilities. This suggests that the prolonged stimulation of the same cognitive ability may generate the greatest benefits in children with ABI.